1476Assessment of Compliance to Indian Tobacco Control Legislation in Northern Hilly State of India. (2nd September 2021) - Aggarwal, Pradeep
Abstract: Background: Parliament of India enacted an act to prohibit advertisement of, and to provide for the regulation of trade and commerce in, and production, supply and distribution of cigarettes and other tobacco products – COTPA. It has been now more than 15 years of this act is in place and there is need to evaluated compliance of COTPA throughout India, this will help stakeholders and policy makers to understand current implementation status. Aim & Objective: To assess the compliance to COTPA across all districts of a Northern Hilly State of India, Uttarakhand. Methodology: Study Setting: All 13 districts of a Northern Hilly State of India, Uttarakhand. Study Design: Sequential mixed methods study design. Study Period: 06 months (March – August 2019). Geographical Scope (Venues of visit) and Study Population: For Section 4: All the potential public places in each district were divided into 5 broad categories: Eateries; Offices/banks; Educational Institutions; Health Care Facilities; Transit Stations For Section 5, 6 (a), 7, 8 &9: All the points of sale; For Section 6 (b): all educational institutions Quantitative - School going adolescent's students aged 14 – 16 years (class 8th to 10th) enrolled in educational institutions and tobacco product point of sale and its vendors near the educational institution. Survey Tools: Total six survey checklist were used in the survey along with a semi structured questionnaire for students in educational institutions regarding their tobacco use status. A Global Positioning System (GPS) tool to geolocate educational institute and POS within 500 meters of educational institution. All the study tools from 1-6 were created using Open Data Kit (University of Washington) software or EpiCollect5 software and data collection was done using tablets. Ethical Consideration: This survey was an unobtrusive observational study. Hence no prior informed consent from the vendors was taken for making the observation. Along-with, the prior permission was taken from the concerned health authorities (in this case State Tobacco Control Society) for conduction of this survey. Result: The overall compliance to all Sections of COTPA (based upon mean of major compliance indicators) - 75.1. The mean compliance to major indicators of Section 4 of COTPA – 59.4%; Section 5 of COTPA -93.8%; Section6(a) of COTPA -83.2%; Section6(b) of COTPA -66.6%; Section 7, 8, 9 of COTPA -72.3%. Compliance to health warning present on packs were recognized in most of the packs in rural areas (82.2%) and urban areas (81.4%). Compliance with display of no promotional messages was 15.4% in rural. Among different type of tobacco products (PoS), Foreign Made Cigarettes were found to be more compliant (87.0%) while Foreign Made Cigars of tobacco was least compliant (45.8%) to major compliance indicators of Section 6 (a) of COTPA. Conclusions: Overall compliance to COPTA was above 80%. Keywords: Prevention and Care - Policy and Community Interventions This survey has been funded by State Tobacco Control Cell, Government of Uttarakhand.